Grass recruitment constraints along a grazing gradient in Patagonia: N-limitation x adult competition trade-off - Garcia Martinez, Guillermo Carlos; Golluscio, Rodolfo Angel (Elsevier, 2021)
We explored the effect of N addition and adult canopy competition on the recruitment of lost preferred species in the Patagonian steppe, where a decelerated N cycling scenario (sensu Ritchie et al., 1998) had been previously detected. In the first experiment we demonstrated that the preferred scarce grass Bromus pictus has typical traits of Competitive species, while the dominant less preferred Pappostipa speciosa has typical traits of Stress tolerant species (sensu Grime, 1997): B. pictus showed higher maximum Relative Growth Rate, water consumption and competitive ability than P. speciosa. In the second experiment, we proved that without N addition, seedlings of the preferred species showed its maximum survival rate under moderate grazing, where adult competition is lower than under ungrazed conditions and N-limitation is lower than under intense grazing. Instead, with N addition, the survival rate of B. pictus was maximum under intense grazing, where N limitation is maximum and adult competition is minimum. These results suggest that in degraded systems subjected to a decelerating N cycling scenario, the revegetation with preferred species would require recovering soil N levels, and would be more successful in the most degraded sites, where the remnant canopy has low cover.